Continuing education on vaccine calendar for community health agents: Experience report - Santos, Vilma de Nazaré Souza; Alves, Fernanda Cristina Rosa; Siqueira, Yuri Oliveira; Santos, Erlane Ribeiro dos; Antunes, Heloana Monteiro; Barros, Micheli Mayara Souza; Rodrigues, Valéria Pinto (Research, Society and Development, 2024)
Objective: To describe the experience of nursing students about carrying out ongoing education with Community Health Agents on the vaccination schedule. Methodology: This is a descriptive study, with a qualitative approach, of the experience report type, conducted through ongoing education on the vaccination schedule aimed at Community Health Agents in Belém do Pará, the educational activity was carried out in February 2024, with 30 Community Health Agents. Results and Discussion: Community Health Agents were invited to an educational activity at the UMS, in which the vaccination schedule for children, adolescents, pregnant women, adults and the elderly was discussed. Children’s vaccination cards were distributed for better understanding by professionals. In addition to the doses and ages at which vaccinations should be administered, the minimum and maximum time between each dose was addressed in cases of delays. At the end of the activity, vaccination cards were completed, allowing Community Health Agents to understand their understanding and clarify their doubts. Thus, the importance of these professionals for monitoring, guiding and actively seeking out the population regarding vaccination was emphasized. Final Considerations: It is concluded from the experience that the continuing education activity contributed to the training of CHWs on the vaccination schedule. Furthermore, constant updating on the subject is necessary to monitor users’ active search and provide guidance on vaccination to the community.